(untitled) (Research, Society and Development, 2022)
The use of different didactic resources in the teaching process can enable students to learn in a more significant way, in order to make the contents presented by the teacher more studied with contextualized knowledge. The objective of this work was to evaluate the importance of alternative methodologies in science teaching in the teaching process in 7th grade classes. A practice and dynamics were carried out in elementary school II of a public school in the municipality of Limoeiro de Anadia - AL, with the dissection of a video school (worm) being carried out to learn the external and internal morphology of these beings, and demonstrated as main characteristics of the phylum Annelida, then there was an application of a dynamic with questions and answers. A ° was applied with 65 students from two 7-year classes. It was found that in the school practical classes are not applied in the discipline of science. About 92% of the responses were effective for the ease of learning and 8% were not optimized. 90% stated that the application of practices in science teaching is important, 10% did not. 89% responded that they liked the applied pedagogical practice and 11% did not. When asked about the level of contribution of the practical class to learning a lot, 89% responded 9% reasonable and 2% not. In general, note that the use of the practical class directly assists in student learning. It is inferred that the use of alternative methodologies (practice, dynamics, exposure of stuffed animals) has a positive influence on the teaching-learning process.